Synthesis and in Vitro and in Vivo Pharmacological Evaluation of New 4-Aminoquinoline-Based Compounds - Tukulula, Matshawandile; Njoroge, Mathew; Abay, Efrem T.; Mugumbate, Grace C.; Wiesner, Lubbe; Taylor, Dale; Gibhard, Liezl; Norman, Jennifer; Swart, Kenneth J.; Gut, Jiri; Rosenthal, Philip J.; Barteau, Samuel; et al. (American Chemical Society, 2022)
A new class of 4-aminoquinolines was synthesized and evaluated in vitro for antiplasmodial activity against both the chloroquine-sensitive (3D7) and -resistant (K1 and W2) strains. The most active compounds 3c–3e had acceptable cytotoxicity but showed strong inhibition toward a panel of cytochrome P450 enzymes in vitro. Pharmacokinetic studies on 3d and 3e in mice showed that they had moderate half-life (4–6 h) and low oral bioavailability. The front runner compound 3d exhibited moderate inhibition of the malaria parasite on P. berghei infected mice following oral administration (5 mg/kg), achieving reduction of parasitemia population by 47% on day 7.